2015
DOI: 10.3109/01658107.2015.1018443
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Depth Imaging of Central Laminar Thickness in Optic Neuropathy: Comparison with Normal Eyes

Abstract: The purpose of this study was to compare central laminar thickness (LT) among patients with glaucomatous optic neuropathy (GON), patients with non-GON, and normal subjects using enhanced-depth imaging optical coherence tomography (EDI-OCT). Enrolled were 57 patients (n = 64 eyes), including 30 women and 27 men. Three groups were identified: GON (n = 18 eyes), non-GON (n = 16 eyes), and control (n = 30 eyes). The GON group comprised eyes with primary open-angle glaucoma (POAG) (n = 9) and normal-tension glaucom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Thinning of the RNFL is observed in both glaucomatous and chronic AION eyes when compared to healthy control eyes [11, 13, 19, 20, 32‒34]. In early/preperimetric glaucoma, the RNFL thinning is observed in the superotemporal and inferotemporal region while moderate glaucoma also involved the temporal RNFL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thinning of the RNFL is observed in both glaucomatous and chronic AION eyes when compared to healthy control eyes [11, 13, 19, 20, 32‒34]. In early/preperimetric glaucoma, the RNFL thinning is observed in the superotemporal and inferotemporal region while moderate glaucoma also involved the temporal RNFL.…”
Section: Resultsmentioning
confidence: 99%
“…In both POAG and NAION eyes, two forces that result in sclera and BMO expansion are proposed: one pushing the LC backward and compressing the PT, and another one related to the hoop stress (inner circumferential pressure supported by the peripapillary sclera) [21]. Mechanical stress thus plays an important role in the pathogenesis, but both diseases remain multifactorial [16,34,37]. Other factors include interindividual variability (e.g., the geometry of the eyeball), vascular factors, an abnormally low cerebrospinal fluid pressure in NTG eyes resulting in higher translaminar pressure gradient which could induce posterior LC displacement, a hypercompliant LC in NTG compared to NAION, inflammation, infiltration, toxicity, heredity factors, and a possibly innate deeper LC in NTG eyes compared to healthy and NAION eyes [16,34,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the laminar thickness was thinner in glaucomatous eyes than in the controls due to increased intraocular pressure 13 . Also, it was recently suggested that as compared to the eyes of healthy controls, LC thicknesses were lower in the eyes with non-glaucomatous optic neuropathy 17 . Increased intraocular pressure is thought to disrupt LC hemodynamics due to its mechanical effect on microcirculation in LC 14 , 15 , 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides ocular diseases such as glaucoma, LC has also been investigated in the central nervous system diseases affecting the optic nerve such as Parkinson's disease and MS. It was shown that this important structure which is related with retinal nerve fibers is also affected in patients with these disorders [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%